A.D. Bache papers - Bache, A. D. (Alexander Dallas), 1806-1867.
Correspondence, a journal, scrapbooks of newspaper clippings, a partial index, and miscellaneous material reflecting Bache's service as superintendent of the United States Coast Survey (1843-1867), member of the U.S. Light-House Board, and U.S. superintendent of weights and measures, his work at the Dudley Observatory in Albany, N.Y., and his European trip as president of the proposed Girard College to study educational methods.
Topics include the survey's publication of navigation charts and maps of the East Coast of the U.S., astronomical research, scientific developments, and foreign affairs. Correspondents include John J. Crittenden, John Adolphus Bernard Dahlgren, James Dwight Dana, Charles Henry Davis, George W. Dean, Blandina Bleecker Dudley, Benjamin Apthorp Gould, Joseph Henry, Benjamin Peirce, Benjamin Silliman, Jr., and George E. Waring.
Microfilm edition of part of these papers available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Geography and Map Division.
Library of Congress Prints and Photographs Division.
Scientist, educator, and superintendent of the United States Coast Survey.
Collection material in English.
Keywords: Crittenden, John J. -- 1787-1863 -- Correspondence; Dahlgren, John Adolphus Bernard, -- 1809-1870 -- Correspondence; Dana, James Dwight, -- 1813-1895 -- Correspondence; Davis, Charles Henry, -- 1807-1877 -- Correspondence; Dean, George W. -- 1825-1897 -- Correspondence; Dudley, Blandina Bleecker, -- 1783-1863 -- Correspondence; Gould, Benjamin Apthorp, -- 1824-1896 -- Correspondence; Henry, Joseph, -- 1797-1878 -- Correspondence; Peirce, Benjamin, -- 1809-1880 -- Correspondence; Silliman, Benjamin, -- 1816-1885 -- Correspondence; Waring, George E. -- 1833-1898 -- Correspondence; United States. -- Light-House Board; Dudley Observatory; Girard College -- Presidents; United States Coast Survey; Astronomy -- Research; Discoveries in science; Education -- Europe -- Methodology; International relations; Navigation -- Atlantic Coast (U.S.); Weights and measures -- United States; Atlantic Coast (U.S.) -- Maps; Europe -- Description and travel; Educators; Scientists